BAKHTINIAN DIALOGICS AND SIGN INTERPRETATION: Mikhail Bakhtin and Charles Peirce (Revista Diálogos, 2015)
This article aims at presenting central concepts in the sign sciences reading Bakhtin’s philosophy of language with Peirce’s semiotics. Insofar as the sign models proposed are dialectic and dialogic, they account for the live processes of semiosis in contrast to glottocentric and anthropocentric orientations. From different perspectives both philosophers evidence the open and dynamic nature of signs and sign activity, their processual nature as material in becoming in open-ended fluxes of infinite semiosis, the connection between signs and values, the centrality of dialogic otherness in interpretive/translative processes, the implications for verbal and nonverbal semiosis, specifically for our conceptions of language, communication, body, and self. This essay develops around the following topics: sign, text, utterance; the dialogic nature of the sign “self”; reading together Bakhtin and Peirce; dialogue and argumentation; dialogism and the voice; dialogism and otherness in the “great experience”; dialogism and critique of identity; the grotesque body and its signs.Este artigo tem como objetivo apresentar conceitos centrais nas ciências dos signos lendo a filosofia da linguagem de Bakhtin juntamente com a semiótica de Peirce. Na medida em que os modelos de signos propostos são dialéticos e dialógicos, eles representam os processos vivos de semiose, em contraste com as orientações glotocêntrica e antropocêntrica. A partir de diferentes perspectivas, os dois filósofos evidenciam a natureza aberta e dinâmica dos signos e da atividade sígnica, sua natureza processual como material em constante transformação e em indeterminados fluxos de semiose infinita, a conexão entre signos e valores, a centralidade da alteridade dialógica em processos interpretativos/translativos, as implicações para a semiose verbal e não verbal, especificamente para as nossas concepções de linguagem, comunicação, corpo e “eu”. Este ensaio se desenvolve em torno dos seguintes temas: signo, texto, enunciado, a natureza dialógica do signo "eu"; leitura conjunta de Bakhtin e Peirce; diálogo e argumentação; dialogismo e a voz; dialogismo e alteridade na "grande experiência"; dialogismo e crítica da identidade; o corpo grotesco e seus signos.